2010
DOI: 10.1590/s0103-64402010000500008
|View full text |Cite
|
Sign up to set email alerts
|

Fracture process characterization of fiber-reinforced dental composites evaluated by optical coherence tomography, SEM and optical microscopy

Abstract: This study used optical coherence tomography (OCT) compared to scanning electron microscopy (SEM) and optical microscopy (OM) to evaluate qualitatively crack propagation and final fracture in restorative composite materials -Filtek Z250 and Filtek Z350 (3M ESPE) -with fiber reinforcement after cyclic loading. Samples were made using a split mold. Initially, 3-point bending tests were performed to determine the maximum force and tension at the fracture moment using samples without fiber reinforcement. Then, mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…In addition, OCT was reported to have better visualization than SEM and optical microscopy. 31 In our study, OCT showed lower adaptation values than the replica technique, with both values being within clinically acceptable limits. This could be related to the different flowing characteristics of the measured surfaces: light-body silicone for replica technique and luting cement for OCT.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In addition, OCT was reported to have better visualization than SEM and optical microscopy. 31 In our study, OCT showed lower adaptation values than the replica technique, with both values being within clinically acceptable limits. This could be related to the different flowing characteristics of the measured surfaces: light-body silicone for replica technique and luting cement for OCT.…”
Section: Discussionsupporting
confidence: 60%
“…31,32,35 According to these reports, OCT provided similar results compared with other techniques. In addition, OCT was reported to have better visualization than SEM and optical microscopy.…”
Section: Discussionmentioning
confidence: 67%
“…To the best of our knowledge, this is the first study conducted with OCT technique to characterize RRC. OCT technology has given valuable information of clinical use of dental materials, 16,17 being also capable of evaluating carious teeth. The alterations in the CEJ and DEJ identified by OCT analysis seem to be the first described.…”
Section: Discussionmentioning
confidence: 99%
“…20 Some studies analyzed periodontal structures, suggesting the possibility of applying OCT to periodontal diagnostics, [21][22][23][24] but evidence is not yet sufficient, especially related to the gingival sulcus, which is an important parameter of periodontal health and disease. Furthermore, OCT has been applied to evaluate dental materials, [25][26][27][28] with the advantages of being a non-destructive imaging technology and rendering three-dimensional (3D) images in real-time acquisition mode.…”
mentioning
confidence: 99%